Polyfunctionalized α-Phenyl-tert-butyl(benzyl)nitrones: Multifunctional Antioxidants for Stroke Treatment - Daniel Diez-Iriepa; Damijan Knez; Stanislav Gobec; Isabel Iriepa; Cristóbal de los Ríos; Isaac Bravo; Francisco López-Muñoz; José Marco-Contelles; Dimitra Hadjipavlou-Litina (MDPI AG, 2022)
Nowadays, most stroke patients are treated exclusively with recombinant tissue plasminogen activator, a drug with serious side effects and limited therapeutic window. For this reason, and because of the known effects of oxidative stress on stroke, a more tolerable and efficient therapy for stroke is being sought that focuses on the control and scavenging of highly toxic reactive oxygen species by appropriate small molecules, such as nitrones with antioxidant properties. In this context, herein we report here the synthesis, antioxidant, and neuroprotective properties of twelve novel polyfunctionalized α-phenyl-tert-butyl(benzyl)nitrones. The antioxidant capacity of these nitrones was investigated by various assays, including the inhibition of lipid peroxidation induced by AAPH, hydroxyl radical scavenging assay, ABTS+-decoloration assay, DPPH scavenging assay, and inhibition of soybean lipoxygenase. The inhibitory effect on monoamine oxidases and cholinesterases and inhibition of β-amyloid aggregation were also investigated. As a result, (Z)-N-benzyl-1-(2-(3-(piperidin-1-yl)propoxy)phenyl)methanimine oxide (5) was found to be one of the most potent antioxidants, with high ABTS+ scavenging activity (19%), and potent lipoxygenase inhibitory capacity (IC50 = 10 µM), selectively inhibiting butyrylcholinesterase (IC50 = 3.46 ± 0.27 µM), and exhibited neuroprotective profile against the neurotoxicant okadaic acid in a neuronal damage model. Overall, these results pave the way for the further in-depth analysis of the neuroprotection of nitrone 5 in in vitro and in vivo models of stroke and possibly other neurodegenerative diseases in which oxidative stress is identified as a critical player.